Understanding Compulsive Buying of Fast-fashion Through Personality, Hedonic Shopping, and Self-Esteem in Indonesia - Sayla Salsabila Nazilah Ali; Rifelly Dewi Astuti (Journal of Consumer Sciences, 2026)
Background: The rapid growth of fast-fashion in Indonesia is fueled by easy consumer access and constantly updating trends. This accessibility, combined with emotional and psychological factors such as personality and self-esteem, has contributed to the rise of compulsive buying behavior, particularly through hedonic shopping experiences. Purpose: This study examines the influence of the Big Five Personality Traits on compulsive buying, with hedonic shopping experience and self-esteem as potential mediators. Method: A quantitative descriptive approach was used to survey 462 respondents who purchased fast-fashion items in the past 2 months. Purposive sampling and PLS-SEM with SmartPLS 4 were used for analysis. Findings: The study reveals that neuroticism, openness to experience, and conscientiousness significantly influence compulsive buying, while extraversion and agreeableness do not. Hedonic shopping experience mediates the relationship between personality traits and compulsive buying for neuroticism, openness, and conscientiousness, but not agreeableness. Self-esteem does not mediate this relationship, suggesting that other factors have a stronger influence on compulsive buying. Conclusions: The study highlights the critical role of hedonic shopping in mediating the influence of personality on compulsive buying, whereas self-esteem serves primarily as a protective factor rather than a mediator. Individuals with high neuroticism or openness are particularly susceptible to hedonic-driven compulsive consumption in the fast-fashion context. Research implication: This study underscores the importance of hedonic shopping in driving compulsive buying in fast-fashion. It suggests that businesses should focus on emotional marketing while promoting responsible consumption. For consumers, the findings highlight the need for mindful consumption to mitigate the negative impacts of compulsive buying.